Proposição de fragmentos de anticorpo de domínio variável (scFv) anti-CD20 para o desenvolvimento de bispecíficos t-cell engager (BiTE) - Pontes, Larissa Queiroz (2023)
Cancer is a pathology characterized by uncontrolled proliferation of cells that can occur in different tissues. It is urgent that drug development should be capable of mitigate, reduce symptoms or prevent metastasis. Thereby the aforementioned, immunotherapy happens to be one of the most successful strategies on cancer treatment. Rituximab is a monoclonal antibody used on lymphoma treatment. Its mechanism of action relies on binding capacity on CD20 protein, expressed on B lymphocytes, leading to depletion. One of the alternatives to strengthen immune system on tumor treatment is bispecifics, which are antibodies that bind to two different epitopes. Bispecific T-Cell Engager (BiTEs) are composed by two scFv’s gathered by a polypeptide linker and they are able to bring together T cells and tumor cells without MHC presentation. The present work proposes higher affinity-antibody fragments in order to develop new anti-CD20 BiTEs. 7 mutant sequences were acquired previously, besides the Rituximab’s wild-type scFv sequence. There was performed an investigation about SUMO tag influence on binding activity and the antibody fragments folding in pET28a vector have been evaluated, where it was observed that SUMO tag was indeed essential to correct folding. Flow cytometry was performed to analyze binding among mutant antibody fragments, BsAbs and CD20 molecule expressed in Raji cells membrane, where it was possible to observe binding only for the entitled fragments NHA, JHA and CicHA. An interferometry assay was performed to quantify kinetic interaction of proteins. The affinity constant obtained was 7,23 μM for MabThera; 1,46 μM for NHA; 0,57 μM for JHA and 0,43 μM for CicHA, confirming flow cytometry data. Thereby, wild-type sequence in anti-CD20xCD3 BiTE format was acquired and the mutant sequences were cloned into pETSUMO vector, expressed in E.coli SHUFFLE T7 and purified automatically in AKTA chromatographer. Protein immunodetection was performed by Western Blot technique using anti-HA-AP as the secondary antibody. This assay revealed scFv’s and bispecifics presence. Therefore, we conclude that CiCHA mutante presented 3-fold affinity higher than wild-type Rituximab’s sequence in scFv format. In this sense, it is a good target for development of BiTEs which can be used to treat blood cancers.